Project Management for Environmental, Construction and Manufacturing Engineers A Manual for Putting Theory into Practice - Munier, Nolberto; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2013)
As a companion to books on project-management theory, this book illustrates, in a down-to-earth, comprehensive style, how to put that theory into practice. It shows not only what needs to be done, but how to do it. In addition to the many examples that illustrate procedures, the book includes over 25 case studies, each one addressing a specific theme. Key topics, such as: project selection negotiations planning and scheduling cost and budgeting project control communications human resources environmental impacts risk management financial evaluation are discussed in project simulations based on real-life situations from a diversity of fields, using a step-by-step approach. Beginning at the grassroots level, some cases are solved by hand to illustrate the mechanics of a procedure, while others are solved using advanced computer programs. In this way the reader has a clear idea of the problem, how and when to raise the issue, information needed (and who can provide it), how to solve it by hand, when possible, and also its resolution using the latest informatics tools. The author has over 30 years of experience in project management in different countries, working on both large-scale projects with major companies worldwide and with urban/regional planners on local projects. He has written more than 15 books on different facets of engineering, lectured in over 80 technical courses and spoken at numerous international conferences. His engineering experience in large undertakings in such fields as hydro-electricity, mining, the environment, and urban planning provides the reader with a wealth of knowledge on the practical side of project management. This book will be of interest to students in engineering, professionals in the field of project management and project consultants.
Preface -- Introduction And Road Map To Project Management -- Project Innovation And Design -- Leadership And Negotiation For Project Management -- Project Strategic Planning -- Project Impact On The Environment.-.Project Risk Management.-.Project Economic And Financial Evaluation.-.Project Selection And Decision-Making.-.Project Planning And Scheduling.-.Project Materials Management -- Project Communications And Enterprise Resource Planning (ERP) -- Project Cost And Budgeting -- Human Resources Planning In Projects -- Project Safety Management -- Project Quality Management -- Project Monitoring And Project Control -- Project Closing -- Index.
Keywords: Environmental sciences; Industrial engineering; Engineering; Environmental management; Nature Conservation; Management information systems; Environment; Environmental Management; Project Management; Industrial and Production Engineering; Construction Management; Nature Conservation; Business Information Systems